Semiholographic Approach in Calculation of Tunneling Current in Graphene with Deep Impurities - M.B. Belonenko; N.N. Konobeeva (Журнал нано- та електронної фізики)
In this paper, we investigated the influence of deep impurity in graphene on the tunneling current in the contact with a metal. A ballistic current in graphene was calculated. The dependence of current-voltage characteristic of the contact on transition energy between the impurity and the graphene was analyzed.